Bilateral knee prosthetic joint infection: a case report - Alharbi, Yasser M.; Alhumaidi, Ibrahim M.; Alamri, Asim J.; Jamal, Rayan S. (International Journal Of Community Medicine And Public Health, 2025)
Bilateral prosthetic joint infection (PJI) is considered rare and its treatment can be challenging. We present this case report of a 70-year-old male with acute presentation of simultaneous bilateral knee prosthetic joint infection. Initially managed with debridement and implant retention with six weeks of intravenous antibiotics. Six months later presented with left knee pain and swelling with investigations showing left knee prosthetic joint infection and was taken for staged revision arthroplasty. Three weeks following staged revision surgery patient presented with left knee progressive pain and open sinus which then was taken for debridement and polyethylene exchange followed by six weeks of intravenous antibiotics. This case report highlights the prevalence, etiologies and risk factors of simultaneous bilateral PJI. Also discussing available treatment options, antimicrobial therapy durations and some encountered difficulties like infection recurrence.